The response of stromatolites to seismic shocks: Tomboliths from the Palaeoproterozoic Chaibasa Formation, E India - van Loon, A.; Mazumder, Rajat; De, S. (2016)
It is demonstrated here for the first time how Palaeoproterozoic stromatolites survived seismic disturbance of their substrate. The stromatolites under study could have been cyanobacteria or any other photoautotrophic microbes, which formed mats that covered a substrate of very fine-grained sandstones and mudstones of the Chaibasa Fm. in eastern India. The sediments represent a shelf environment. The local abundance of the stromatolites suggests that the low-energy environment formed a suitable habitat. The common phases of tectonic quiescence were, however, occasionally interrupted by seismic shocks. These were sufficiently strong to deform the mat layers, the lower parts of which might already have been (semi-) consolidated. The mats became partly folded, partly faulted, and already consolidated parts of the stromatolite layers broke off. This can be deduced from the angular shapes of part of the broken-off fragments. It appears, however, that part of these fragments were still sufficiently soft to become rounded and deformed by rolling over the seafloor, probably under the influence of tidal currents. When come to rest, these fragments served as a new substrate for new generations of the micro-organisms. These micro-organisms thus survived by continued growth on the reworked fragments and built up new stromatolites that may show an ‘angular disconformity’ with the stromatolites of their substrate. It thus is shown that stromatolites have an adequate response to a sudden disturbance of their habitat, and that they survive earthquakes by colonization of broken-off fragments. We call the ‘healed’ fragments ‘tomboliths’ (tumbled stones).